Comparable efficacy of endoscopic transpapillary gallbladder drainage and percutaneous transhepatic gallbladder drainage in acute cholecystitis - Iino, Chikara (Endosc Int Open, 2018)
BACKGROUND AND STUDY AIMS:  Although endoscopic transpapillary gallbladder drainage (ETGBD) is reportedly useful in patients who have acute cholecystitis, its efficacy has not been compared to that of percutaneous transhepatic gallbladder drainage (PTGBD). We retrospectively compared the efficacy and safety of ETGBD and PTGBD in patients with acute cholecystitis. PATIENTS AND METHODS:  We studied 75 patients who required gallbladder drainage for acute cholecystitis between January 2014 and December 2016. Using propensity score matching analysis, we compared the clinical efficacy and length of hospitalization in patients successfully treated with ETGBD and PTGBD. Moreover, we assessed the predictive factors for hospitalization period < 30 days using multivariate analysis. RESULTS : ETGBD and PTGBD were successfully performed in 33 patients (77 %) and 42 patients (100 %) ( P  < 0.001). Twenty-seven matched pairs were obtained after propensity score matching analysis. No significant differences were observed between patients treated with ETGBD and those treated with PTGBD with respect to improvement in white blood cell count and serum C-reactive protein level. The length of hospitalization in patients treated with ETGBD was significantly shorter than in those treated with PTGBD regardless of the need for surgery. Multivariate logistic regression analysis revealed ETGBD (odds ratio, 7.07; 95 % confidence interval 2.22 – 22.46) and surgery (odds ratio 0.26; 95 % confidence interval 0.09 – 0.79) as independent factors associated with hospitalization period. There were no significant differences in occurrence of complications in ETGBD and PTGBD procedure. CONCLUSIONS : ETGBD was shown to be as useful as PTGBD for treatment of acute cholecystitis and was associated with shorter hospitalization period. ETGBD can be an alternative treatment option for acute cholecystitis at times when PTGBD is not possible.